2021
DOI: 10.3390/rs13081509
|View full text |Cite
|
Sign up to set email alerts
|

Uni-Temporal Multispectral Imagery for Burned Area Mapping with Deep Learning

Abstract: Accurate burned area information is needed to assess the impacts of wildfires on people, communities, and natural ecosystems. Various burned area detection methods have been developed using satellite remote sensing measurements with wide coverage and frequent revisits. Our study aims to expound on the capability of deep learning (DL) models for automatically mapping burned areas from uni-temporal multispectral imagery. Specifically, several semantic segmentation network architectures, i.e., U-Net, HRNet, Fast-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 90 publications
(132 reference statements)
0
30
0
1
Order By: Relevance
“…Several studies have combined SAR and MSI with success in BA assessment [10][11][12][13][14][15][16][17][18][19]. Verhegghen et al, 2016 [19] show that the combined use of Sentinel-2 MSI and Sentinel-1 SAR can be utilized to detect and monitor fire outbreaks.…”
Section: Cnns and Sar In Burnt Area Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have combined SAR and MSI with success in BA assessment [10][11][12][13][14][15][16][17][18][19]. Verhegghen et al, 2016 [19] show that the combined use of Sentinel-2 MSI and Sentinel-1 SAR can be utilized to detect and monitor fire outbreaks.…”
Section: Cnns and Sar In Burnt Area Mappingmentioning
confidence: 99%
“…These advances have enabled researchers to apply CNNs with success in land cover, water and built environment classification tasks [12]. Many of these studies are carried out with fine or medium resolution optical data, often achieving >90% accuracies [13][14][15]. With the launch of the ESA Sentinel-1 satellites, a surge of SAR related research is being published in the context of land cover classification, environmental disturbance monitoring and change detection [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of RS Earth observation imagery and its free availability has meant that monitoring of changes following disasters has turned into a hot topic for research [21][22][23][24][25][26][27][28]. Indeed, we are witnessing many BAM products on a global scale that differ in terms of spatial resolution and reliability of the burned areas mapped.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that Res-U-Net had high efficiency, with a patch-size of 256 × 266. Hu, Ban and Nascetti [26] evaluated the potential of deep learning methods for BAM based on the unitemporal multispectral Sentinel-2 and Landsat-8 datasets. Their study showed that deep-learning methods have a high potential for BAM in comparison to machine-learning methods.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, a burned vegetation index is created for allowing the identification of burned and unburned areas defined on different thresholds after filtering low-quality pixels, and then combining this information with active fires. The use of different auxiliary information as input attribute is also frequent [13]. Very well known methods as random forest [14,15], support vector machines [16,17], artificial neural networks [18], convolutional neural networks with long short term memory (LSTM) [19], BA-Net deep learning method [20], U-net convolutional neural networks [21], geometric semantic genetic programming [22] and XGBoost [23,24] are now popular methods for segmentation of burned regions.…”
mentioning
confidence: 99%